CLINICAL AND EFFECTIVE RISKS OF DISABILITY AMONG VICTIMS OF ROAD TRAFFIC ACCIDENTS - Guryev, S.O.; Yaroviy, D.M. (The Ukrainian Scientific Medical Youth Journal, 2018)
Clinical and effective risks of disability incidence have been determined on the basis of analysis of 219 cases among the victims of road accidents that have suffered from disability. Determination of the clinical outcome of the risk of invalidity among the victims as a result of traffic accidents is an important stage in the development of a comprehensive rehabilitation system aimed at reducing the level and degree of disability among the victims as a result of road traffic accidents. The highest risks are male, age group of which is 46-75, and pedestrians who have been injured with combined trauma mechanisms. The highest risks are the clinic-anatomical groups of the limbs and the backbone, the clinical and nosological groups “KTAST”, “KST”, “KATAT” and the damage, assessed on the scale of ISS from 25 to 75 points. It is necessary and appropriate to adhere to the principle of individualizing the choice and carrying out rehabilitation activities, depending not only on the clinical and nosological characteristics of the injury, but also on the level of the risk of incidence of disability. The peculiarity of the rehabilitation of victims as a result of an accident is the beginning of the rehabilitation process from the stage of unstable adaptation and the need to ensure the continuity of the implementation of rehabilitation measures.